Introducing Indonesian Traditional Dance To Teach Indonesian Language For Foreign Speakers (Bipa) In Thailand - Dian Candra Prasetyanti (Universitas Muhammadiyah Semarang, 2016)
Abstract. Teaching Indonesian language for foreign speakers at Khon Kaen University, Thailand. This was the first Bahasa Indonesia course in Khon Kaen University. Because the learners in this course never knew about Bahasa Indonesia before, so the teacher introduced them about Indonesian traditional dances. This was the best way to attract foreign learners about Indonesian culture and develop their character. They didnt only learn about Indonesian language, but also local culture. The learners in Bahasa Indonesia course were beginner level (A1) so the teacher chose Denok dance from Semarang and Jaranan dance from Central Java. Because the movements in both dances were also in basic level. The class consist of seven students, 3 boys and 4 girls, they are first and second year students. They came from different study programs, such as Nursing, Engineering, Spanish and Germany. The teacher taught Denok dance for the girls and Jaranan dance for the boys. They also learnt about the meaning of the lyric in these dances, the costumes that the teacher brought from Indonesia, such as sampur(shawl), jarit, kebaya, tapih, head band (ikat kepala) and how to use them, how to make Jaranan as the accessory to perform the dance. At the end of the course, they performed the dance on the stage and seen by many teachers and students in Khon Kaen University and the videos had been uploaded inYouTube.